Evaluations of US poetry since 1950. - Von Hallberg, Robert, 1946-; Faggen, Robert (Recencies., 2021)
Horace speaks of poetry delighting and instructing. While Evaluations of US Poetry since 1950, Volume 1 explores the pleasures of poetry--its language, forms, and musicality--volume 2 focuses on the public dimensions.